The pursuit of quantum gravity memoirs of Bryce DeWitt from 1946 to 2004 - DeWitt-Morette, Cécile (Springer Berlin Heidelberg, 2011)
1946 is the year Bryce DeWitt entered Harvard graduate school. Quantum Gravity was his goal and remained his goal throughout his lifetime until the very end. The pursuit of Quantum Gravity requires a profound understanding of Quantum Physics and Gravitation Physics. As G. A. Vilkovisky commented , "Quantum Gravity is a combination of two words, and one should know both. Bryce understood this as nobody else, and this wisdom is completely unknown to many authors of the flux of papers that we see nowadays." Distingished physicist Cecile DeWitt-Morette skillfully blends her personal and scientific account with a wealth of her late husband's often unpublished writings on the subject matter. This volume, through the perspective of the leading researcher on quantum gravity of his generation, will provide an invaluable source of reference for anyone working in the field. "I found the book both instructive and fascinating. Bryce DeWitt and Cécile DeWitt-Morette formed the most creative couple in physics that I have ever read about, heard about or, in this case, been privileged to know. Bryce started work on the problem of quantum gravity in the late 1940s, long before it became fashionable, and continued to make trail-blazing contributions until his death. Cécile, superbly trained and gifted in mathematics as well as physics, made many contributions to other fields of physics and also collaborated with Bryce from time to time. Now she has memorialized him in a way that only she could, framing the documented story of his lifelong quest with an account from her unique vantage point. Fortunately, this includes a discussion of functional integration, a field in which her work is of fundamental significance." John Stachel, Director, Center for Einstein Studies, Boston University These wonderful memoirs were produced by DeWitt's partner-in-life-and-science, Cécile Morette (épouse DeWitt). They contain extracts of DeWitt's own writings, many of them gems, embedded in an expository matrix crafted by Morette that makes the gems shine more brightly. We see Morette making the foundations of DeWitt?s physics (functional integrals) mathematically reliable, we catch brief glimpses of their life together, but mostly we see DeWitt's seminal ideas and discoveries about the laws of nature, placed in a historical and philosophical context. Besides compelling pieces aimed at specialists, these memoirs also contain treasures that will delight and inform the more general reader: Why Physics? (a letter from DeWitt to his grandson about the nature of physics and mathematics, and physicists and mathematicians); documents in which DeWitt transforms a wealthy entrepreneur?s passion for anti-gravity aircraft into a passion for fundamental physics; the history of the Wheeler-DeWitt equation for the wave function of the universe, the history of the Many Worlds (parallel-universes) interpretation of quantum mechanics, and a carefully crafted letter explaining DeWitt's view of researchers whom the establishment labels 'crackpots'. When I picked up this book, I couldn't put it down; I read it cover to cover with enjoyment and delight. Kip Thorne , The Feynman Professor of Theoretical Physics, California Institute of Technology